2020
DOI: 10.1111/rda.13671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vedic music on steroidogenic gene expression in 3D‐cultured buffalo granulosa cell spheroids model system, a pilot study

Abstract: Music is known for reducing stress, anxiety and depression, improving cognitive performance, and enhancing oestrogen levels. However, its effect on non‐auditory mammalian cell system and the molecular events leading to higher oestrogen levels is less explored. Therefore, the present study targeted to know the direct effects of a peaceful Vedic music on 3D cultured buffalo granulosa cell spheroids. The spheroids were daily exposed to the Mahamrityunjaya mantra, a kind of Vedic chants, for 1.5 hr for 6 days. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It has been shown that Indian Vedic music can upregulate the expression of steroidogenic genes in 3D cultured buffalo granulosa cell spheroids (Pandey et al 2021).…”
Section: Effects On Genomementioning
confidence: 99%
“…It has been shown that Indian Vedic music can upregulate the expression of steroidogenic genes in 3D cultured buffalo granulosa cell spheroids (Pandey et al 2021).…”
Section: Effects On Genomementioning
confidence: 99%
“…It has been shown that Indian Vedic music can upregulate the expression of steroidogenic genes in 3D cultured buffalo granulosa cell spheroids (Pandey et al 2021).…”
Section: Effects On Genomementioning
confidence: 99%
“…[ 3 ] However, recently group-level studies conducted by Indian researcher (2020) for mantra sounds have proven to increase immunity, reduce stress, and affect the expression analysis of steroidogenic ( CYP19A1 , STAR , and HSD17β1 ) and proliferative marker ( PCNA ) gene upregulation in short durations. [ 4 ]…”
mentioning
confidence: 99%